Plasma chemistry-- 2 : plasma chemistry and transport phenomena in thermal plasmas - Bell, A. T.; Bonet, C. (Pergamon Press, 1976)
Plasma Chemistry - 2: Plasma Chemistry and Transport Phenomena in Thermal Plasmas presents the proceeding of the Second International Symposium on Plasma Chemistry, held in Rome, Italy, on September 18-23, 1975. This book discusses the thermodynamic state of chemically reacting plasmas, which are generally described by Pauli or Boltzmann kinetic equations. Organized into eight chapters, this compilation of papers begins with an overview of the influence of the plasma state by a superimposed laser radiation field. This text then examines the mechanisms of chemical transformations in electric di.